Data Safe Havens in health research and healthcare. (25th June 2015) - Burton, Paul R.; Murtagh, Madeleine J.; Boyd, Andy; Williams, James B.; Dove, Edward S.; Wallace, Susan E.; Tassé, Anne-Marie; Little, Julian; Chisholm, Rex L.; Gaye, Amadou; Hveem, Kristian; Brookes, Anthony J.; et al.
Abstract : Motivation: The data that put the 'evidence' into 'evidence-based medicine' are central to developments in public health, primary and hospital care. A fundamental challenge is to site such data in repositories that can easily be accessed under appropriate technical and governance controls which are effectively audited and are viewed as trustworthy by diverse stakeholders. This demands socio-technical solutions that may easily become enmeshed in protracted debate and controversy as they encounter the norms, values, expectations and concerns of diverse stakeholders. In this context, the development of what are called 'Data Safe Havens' has been crucial. Unfortunately, the origins and evolution of the term have led to a range of different definitions being assumed by different groups. There is, however, an intuitively meaningful interpretation that is often assumed by those who have not previously encountered the term: a repository in which useful but potentially sensitive data may be kept securely under governance and informatics systems that are fit-for-purpose and appropriately tailored to the nature of the data being maintained, and may be accessed and utilized by legitimate users undertaking work and research contributing to biomedicine, health and/or to ongoing development of healthcare systems. Results: This review explores a fundamental question: 'what are the specific criteria that ought reasonably to be met by a data repository if it is to be seen as consistent with this interpretation and viewed as worthy of being accorded the status of 'Data Safe Haven' by key stakeholders'? We propose 12 such criteria. Contact: paul.burton@bristol.ac.uk